Welcome to the Journal of Amateur Sport! - Bass, Jordan R. (Journal of Amateur Sport, 2015)
We hope you enjoy the second issue of the Journal of Amateur Sport (JAS)! We are quite excited by the wide-range of articles in the issue and believe there is “something” for everyone in the pages that follow. In the coming months, we will release our first special issue guest edited by Drs. Kyle Bunds and Joshua Newman. Please keep an eye out for the release of that issue in early 2016 and the third standard issue of JAS in the spring of 2016. Thanks a ton for reading and I hope you find value in the excellent articles that comprise this issue.